Analisis Perbedaan Faktor-Faktor Yang Mempengaruhi Financial Performance Di Indonesia Dan Asia Tenggara - Hariadi, Sugeng (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
Financial Performance is one measure of financial performance that can describe the achievements of a company that is sourced from financial statement. Management achievement is reflected in the financial statements measured through earnings. And profitability in this study is reflected through ROA. While the independent variables measured in this study are CAR, LDR, NPL, DER and BOPO. The measurement results of independent and bound variables are compared between those in Indonesia and those in ASEAN. The purpose of the study was to determine whether or not there was a difference in influence and how much difference the influence of the variables CAR, LDR, NPL, DER and BOPO on financial performance for banks listed on the IDX and the ASEAN Stock Exchange. The sample in this study is banks that are listed on the IDX (42), while those in ASEAN Stock Exchange (82). From the analysis that exists, globally on the banking objects listed on the BEI and ASEAN show that there are differences in the partial effect of the CAR, LDR, DER, NPL and BOPO variables, there are differences in influence on the Indonesia Stock Exchange and the State Stock Exchange ASEAN both partially and simultaneously.